Substantivity of mouth-rinse formulations containing cetylpyridinium chloride and O-cymen-5-ol: a randomized-crossover trial - Felipe-Rodrigo Aguilera; Miguel Viñas; Josep M. Sierra; Teresa Vinuesa; Antonio R. Fernandez de Henestrosa; Marta Furmanczyk; Carles Trullàs; Eric Jourdan; José López-López; Marta Jorba (BMC, 2022)
Abstract Background The efficacy of mouth-rinses strongly depends upon their substantivity. The use of natural and non-toxic products that avoid secondary effects is gaining interest in preventive dentistry. The purpose of this study was to evaluate the substantivity of two formulations of mouth-washing solutions based on cetylpyridinium (CPC) and O-cymen-5-ol. Methods This was a randomized, double-blind, crossover trial conducted at the Faculty of Medicine and Health Sciences of the University of Barcelona. Bacterial re-colonization was followed by live/dead (SYTOTM9 + propidium iodide) bacterial staining and measured by confocal laser scanning microscopy and fluorometry. Unstimulated saliva samples were collected from 16 healthy individuals at baseline saliva and then, at 15 min, 30 min and 1, 2, 3, and 4 h after the following mouth-rinses: (i) a single, 1-min mouth-rinse with 15 ml of placebo (negative control); (ii) a single, 1-min mouth-rinse with 15 ml of CPC (0.05%) ; (iii) a single, 1-min mouth-rinse with 15 ml of O-cymen-5-ol (0.09%); (iv) a single, 1-min mouth-rinse with 15 ml of CPC (0.05%) + O-cymen-5-ol (0.09%). Results Proportion of dead bacteria was significantly higher for all mouthrinses during the first 15 min compared to baseline (CPC = 48.0 ± 13.9; 95% CI 40.98-56.99; p < 0.001, O-cymen-5-ol = 79.8 ± 21.0; 95% CI 67.71-91.90; p < 0.05, CPC + O-cymen-5-ol = 49.4 ± 14; 95% CI 40.98-56.99; p < 0.001 by fluorometry and 54.8 ± 23.0; 95% CI 41.50-68.06; p < 0.001, 76.3 ± 17.1; 95% CI 66.36-86.14; p < 0.001, 47.4 ± 11.9; 95% CI 40.49-54.30; p < 0.001 by confocal laser scanning microscopy, respectively). Nevertheless, after 4 h, CPC + O-cymen-5-ol was the only one that obtained significant values as measured by the two quantification methods used (80.3 ± 22.8; 95% CI 67.15-93.50; p < 0.05 and 81.4 ± 13.8; 95% CI 73.45-89.43; p < 0.05). The combined use of CPC + O-cymen-5-ol increased the substantivity of the mouthrinse with respect to mouthrinses prepared with either of the two active products alone. Conclusion The synergistic interaction of CPC and O-cymen-5-ol prolongs their substantivity. The resulting formulation may be as effective as other antimicrobials, such as triclosan or chlorhexidine, but without their undesirable secondary effects. Thus, mouthrinsing products based on Combinations of CPC and O-cymen-5-ol may replace in the near future Triclosan and Chlorhexidine-based mouthrinses.